Readability and Quality of English and Spanish Online Health Information about Cochlear Implants. Issue 3 (31st March 2023) - Nix, Evan; Willgruber, Abbigayle; Rawls, Chase; Kinealy, Brian P.; Zeitler, Daniel; Schuh, Marissa; Bush, Matthew
Abstract : Objective: According to the American Medical Association, Internet web site health information should be written at or below a 6th grade reading level. The purpose of this study was to evaluate the readability and quality of cochlear implant web site health information. Study Design: Cross-sectional web site analysis. Setting: Four Internet search engines involving the top 200 web sites (English and Spanish). Intervention/Methods: "Cochlear implant" was queried in four Internet search engines, and the top 200 English and Spanish web sites were aggregated. After removing duplicates, the web sites were evaluated for readability by using the following validated online readability calculators: Flesch Reading Ease score for English web sites and the Fernandez–Huerta Formula for Spanish web sites. Information quality was assessed using the validated DISCERN quality criteria and the presence of Health on the Net Code of Conduct (HONcode) certification. Results: A total of 80 non-industry-sponsored (43 English and 37 Spanish) and 11 industry-sponsored (4 English and 7 Spanish) cochlear implant health information web sites were included in the study. English web sites were written at a higher reading level (mean = 50.88, SD = 11.98) compared with Spanish web sites (mean = 59.79, SD = 6.04) ( p < 0.01). For both English and Spanish web sites, these scores correlate to the reading level of the average 10th to 12th grade student. Only 12% of Spanish web sites and 27% of English web sites were HONcode certified. The average DISCERN quality score was 41.67 for English web sites and 43.46 for Spanish, indicating significant concerns for quality. There was no association found between readability and quality of the web sites analyzed. Conclusions: Patient-directed English and Spanish web sites regarding cochlear implantation were written at reading levels that significantly exceed those recommended by the AMA. Furthermore, these web sites have significant quality shortcomings. Patients would benefit from more rigorous editing to improve readability and quality of content.